2019
DOI: 10.18502/ijrm.v17i3.4516
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification has detrimental effects on maturation, viability, and subcellular quality of oocytes post IVM in cancerous women: An experimental study

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is unclear if our enriched culture system could be the cause for the relatively low survival rates following vitrification. It has been postulated that IVM oocytes are more susceptible to vitrification, and several reports have described the negative effects of vitrification on oocyte survival when IVM is involved [ 33 , 34 ]. However, as data on survival rates after vitrification and warming from oocytes and embryos after IVM in oncological patients are scarce, evaluation on its efficacity is currently unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if our enriched culture system could be the cause for the relatively low survival rates following vitrification. It has been postulated that IVM oocytes are more susceptible to vitrification, and several reports have described the negative effects of vitrification on oocyte survival when IVM is involved [ 33 , 34 ]. However, as data on survival rates after vitrification and warming from oocytes and embryos after IVM in oncological patients are scarce, evaluation on its efficacity is currently unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…Though successful birth after cryopreservation of germinal vesicle (GV)-stage oocytes with IVM has been reported in 1998 [ 139 ], concerns regarding higher rates of chromosomal abnormalities of immature oocytes after cryopreservation exist [ 140 ]. It has been found that vitrification of immature oocytes before IVM can adversely influence oocyte maturation, viability, and subcellular oocyte quality [ 87 ]. A meta-analysis based on 14 studies that assessed maturation rate after vitrification of metaphase I (MI)/ GV oocytes concluded that oocyte vitrification decreased the maturation rate by 24% [ 141 ].…”
Section: Cryopreservation and Other Physical Factorsmentioning
confidence: 99%
“…As a result, unconventional ovarian stimulation protocols may be used, which have not yet been confirmed to be comparable with classical protocols. Often, the only option remains cryopreservation after in vitro oocyte maturation, which further adds unevaluated factors to the fertility potential of such oocytes [ 12 ].…”
mentioning
confidence: 99%